Exploring the naturally acquired response to Pvs47 gametocyte antigen - Soares da Veiga, Gisele Tatiane; Donassolo, Rafael Amaral; Forcellini, Sofia; Ferraboli, Julia Weber; Kujbida Junior, Mario Antonio; Nisimura, Líndice Mitie; Bassai, Letícia Werzel; Kessler, Rafael Luis; Serpeloni, Mariana; Bittencourt, Najara Carneiro; Salazar, Yanka Evellyn Alves R.; Guimarães, Luiz Felipe Ferreira; et al. (Frontiers in Immunology, 2024)
Malaria represents a challenging global public health task, with Plasmodium vivax being the predominant parasite in Brazil and the most widely distributed species throughout the world. Developing a vaccine against P. vivax malaria demands innovative strategies, and targeting gametocyte antigens shows promise for blocking transmission prevention. Among these antigens, Pvs47, expressed in gametocytes, has shown remarkable efficacy in transmission blocking. However, remains underexplored in vaccine formulations. This study employed in silico methods to comprehensively characterize the physicochemical properties, structural attributes, epitope presence, and conservation profile of Pvs47. Additionally, we assessed its antigenicity in individuals exposed to malaria in endemic Brazilian regions. Recombinant protein expression occurred in a eukaryotic system, and antigenicity was evaluated using immunoenzymatic assays. The responses of naturally acquired IgM, total IgG, and IgG subclasses were analyzed in three groups of samples from Amazon region. Notably, all samples exhibited anti-Pvs47 IgM and IgG antibodies, with IgG3 predominating. Asymptomatic patients demonstrated stronger IgG responses and more diverse subclass responses. Anti-Pvs47 IgM and IgG responses in symptomatic individuals decrease over time. Furthermore, we observed a negative correlation between anti-Pvs47 IgM response and gametocytemia in samples of symptomatic patients, indicating a gametocyte-specific response. Additionally, negative correlation was observed among anti-Pvs47 antibody response and hematocrit levels. Furthermore, comparative analysis with widely characterized blood antigens, PvAMA1 and PvMSP119, revealed that Pvs47 was equally or more recognized than both proteins. In addition, there is positive correlation between P. vivax blood asexual and sexual stage immune responses. In summary, our study unveils a significant prevalence of anti-Pvs47 antibodies in diverse Amazonian samples and the importance of IgM response for gametocytes depuration. These findings regarding the in silico characterization and antigenicity of Pvs47 provide crucial insights for potential integration into P. vivax vaccine formulations.